Evaluation of the value of p53 protein expression in the extra-capsular extension of prostate cancer - Saidi, S; Georgiev, V; Stavridis, S; Penev, M; Stankov, O; Dohcev, S; Banev, S; Danilovski, D; Ivanovski, O; Popov, Z (My University, 2011)
The objective of this study is to identify the nuclear expression of the p53 protein in prostate cancer and to determine its relationship with clinico-pathological variables.